Bifunctional regenerated cellulose membrane containing TiO2 nanoparticles for absorption and photocatalytic decomposition - Yang, Evyan Chia Yan; Sarani Zakaria,; Chin, Hua Chia; Rosenau, Thomas (Penerbit Universiti Kebangsaan Malaysia, 2017)
A simple and green method was presented to embed TiO2 on regenerated cellulose membranes via cellulose dissolution-regeneration process. The physical, chemical and mechanical properties of the composite membranes were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier- Transform Infrared (FTIR), ultraviolet (UV) - visible spectroscopy and tensile test. The results indicated that cotton linter has been converted from cellulose I to cellulose II after the regeneration process, while the TiO2 nanoparticles embedded inside the membrane maintaining its original crystal structures. The TiO2 composite membranes possessed high ability of water absorption with total pore volume ranged from 0.45±0.01 to 0.53±0.02 cm3/g. The elongation at break of the prepared membranes increased 29% averagely from dry state to wet state. The tensile strength of the membranes remained at a minimum value of 0.50±0.03 MPa in wet state thus enabled the films to withstand in wet for long period of time under weak UV irradiation. The regenerated cellulose membranes with TiO2 performed well in photocatalytic activity while exhibiting distinct absorption abilities. This study provides a potential application in energy-saving decomposition system in which the dye compound can be easily removed via two simultaneous pathways: Absorption and photocatalytic decomposition.